VD_FINDINFO Décision / 2013 / 847 vom 21. August 2012 - VD Tribunal cantonal (2012)
INDEMNITÉ POUR DÉTENTION, AVOCAT, HONORAIRES, CLASSEMENT DE LA PROCÉDURE | 363 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 430 CPP (CH)